Studi Pendidikan Satu Atap - Hadiqoh Asmuni (MUNAQASYAH : Jurnal Ilmu Pendidikan dan Pembelajaran, 2021)
Abstract One Roof School Education (Satap) is a government policy made in the success of compulsory education. This education is centered in isolated, remote and scattered areas from other educational institutions, making it difficult for access to continue to higher level schools. The aims of this research are to: (1) describe the one-stop educational innovation model; (2) describe the role of stakeholders in the implementation of one roof education; (3) describe the characteristics of one-roof education. The method used is a qualitative method with a phenamonological approach, namely the researcher wants to know the essential phenomena and experiences of participants, and wants to explore more deeply about a program, process and participant activity. The research findings show that (1) the one-roof school (Satap) is a discovery innovation that needs to be done to help areas whose access to continue to the next level is constrained by distance and cost; (2) The role of stakeholders in education can be applied to various types of activities, adjusted to the policies and abilities of each party. (3) One-roof schools (Satap) are very useful and have good values ​​for prospective students in particular and managers, besides that they also have a level of conformity related to the application of values ​​in the educational process that exists in each educational unit at each level.